(untitled) (Scientific journal of the Fergana State University, 2023)
The article describes the fact that phraseological units, like lexemes, have an internal structure consisting of relations between form and content, that the content structure, together with denotative, connotative and pragmatic semes, contains a seme of any part of speech as well, and phraseological units occupy a syntactic position characteristic to the group which they belong to.